Defining Insanity: How an Individual's View Can Impact a Trial - Jayme L Ayres (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2020)
The insanity plea has always been a controversial topic among anyone. No one sees eye to eye on the matter. This can present a problem within professional fields. When insanity cases are brought into courtrooms, legal and psychology professionals need to be able to agree to some extent. However, these professionals have no true control on how jurors define insanity. Jurors tend to determine guilty or not guilty in insanity cases, based on their own personal views. The current study is a replication of Doctor John Geiger’s 2003 and 2008 study of how legal professionals and undergraduate psychology students view the seven different definitions of insanity. In this article it will show how undergraduate criminal justice and psychology students define and view insanity.
Keywords: insanity plea; mental illness; diverse backgrounds; onset controllability